RESPONSE OF POST HARVEST TREATMENTS ON NUTRITIONAL CHARACTERISTICS AND SHELF LIFE OF LITCHI (cv. DEHRADUN) - RESHI, MONICA; KAUL, RAJ KUMARI; BHAT , ANJU; K. SHARMA, SATISH (The Bioscan, 2013)
Cultivar performance of litchi (Litchi chinensis Sonn.) and roles of water loss, browning and calcium in post harvest fruit senescence were studied; different combinations of post harvest treatments applied showed a great influence in retaining the nutritional characteristics which reduce the wastage of fresh fruits. Storage studies revealed that over a period of 10 days at (32+ 3°C), a continuous and significant decline in physiological loss in weight from 1.33% to 5.08%, acidity (0.41% to 0.22%) and ascorbic acid (42.64 to 25.71mg/100m1) was recorded, whereas, a gradual increase in TSS from 20.17 Brix to 26.64Brix (up to 6 days) and then decrease to 17.06 Brix (upto 10 days). Thus it can be inferred from the study that calcium extends the shelf-life of fruit by maintaining firmness. Minimizing the rate of respiration, disintegration of tissues and disease incidence while as sulphur maintains the colour of the fruit.